2018
DOI: 10.3892/ol.2018.8130
|View full text |Cite
|
Sign up to set email alerts
|

Potential tumor suppressing role of microRNA-545 in epithelial ovarian cancer

Abstract: Epithelial ovarian cancer (EOC) is the most common type of ovarian cancer, which exhibits invasive traits. MicroRNAs (miRNAs/miRs) have been demonstrated to serve important functions in the pathogenesis of EOC. However, the function of miR-545 in EOC remains unknown. In the present study, the function of miR-545 in EOC was analyzed and it was identified that miR-545 is downregulated in EOC tissues and cell lines. Additionally, a low level of miR-545 expression was associated with a low survival rate of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 38 publications
4
20
0
Order By: Relevance
“…In EOC, miR-545-3p is downregulated in EOC tissues and cell lines [34]. Patients with EOC characterized by low miR-545-3p expression have a shorter overall survival compared with patients exhibiting high miR-545-3p expression [34]. Consistent with this result, the decrease of miR-545-3p expression in EOC was veri ed in our study and its upregulation suppressed cell growth and metastasis by directly targeting HDAC4.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In EOC, miR-545-3p is downregulated in EOC tissues and cell lines [34]. Patients with EOC characterized by low miR-545-3p expression have a shorter overall survival compared with patients exhibiting high miR-545-3p expression [34]. Consistent with this result, the decrease of miR-545-3p expression in EOC was veri ed in our study and its upregulation suppressed cell growth and metastasis by directly targeting HDAC4.…”
Section: Discussionsupporting
confidence: 87%
“…Differentially expressed miR-545-3p has been observed in diverse human malignancies [46][47][48]. In EOC, miR-545-3p is downregulated in EOC tissues and cell lines [34]. Patients with EOC characterized by low miR-545-3p expression have a shorter overall survival compared with patients exhibiting high miR-545-3p expression [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the environmental deterioration and other factors, a younger trend of breast cancer occurrence has been shown in recent years 20 The radical surgical resection, combined with radiotherapy and chemotherapy, marks the improvement regarding the survival time of early breast cancer patients, but its therapeutic effect is not satisfactory on advanced breast cancer patients 21 miRNA, as a kind of endogenous small noncoding RNA, plays an important role in cell differentiation, proliferation, and apoptosis through regulating the signaling pathway. Accumulative evidences indicate that a variety of miRNAs are involved in the regulation process of several tumors and play similar roles to tumor suppressor genes and oncogenes 22,23 The abnormal expressions of miR-21 and miR-205 are possibly related to the occurrence and development of breast cancer 12 Li et al 24 found that the miR-205 expression level is increased in epithelial ovarian cancer, and is closely related to the proliferation and invasion of ovarian cancer. In this study, we found that the level of miR-205-3p was significantly upregulated in breast cancer tissues, and further in vitro assay by overexpressing miR-205-3p validated its role on proliferation, invasion, and apoptosis of cancer cells, which was in line with previous findings 24 .…”
Section: Discussionmentioning
confidence: 99%
“…at the age of 45-65 years. Accumulative evidences indicate that a variety of miRNAs are involved in the regulation process of several tumors and play similar roles to tumor suppressor genes and oncogenes22,23 The abnormal expressions of miR-21 and miR-205 are possibly related to the occurrence and development of breast cancer12 Li et al 24 found that the miR-205 expression level is increased in epithelial ovarian cancer, and is closely related to the proliferation and invasion of ovarian cancer. Accumulative evidences indicate that a variety of miRNAs are involved in the regulation process of several tumors and play similar roles to tumor suppressor genes and oncogenes22,23 The abnormal expressions of miR-21 and miR-205 are possibly related to the occurrence and development of breast cancer12 Li et al 24 found that the miR-205 expression level is increased in epithelial ovarian cancer, and is closely related to the proliferation and invasion of ovarian cancer.…”
mentioning
confidence: 99%